Answers

2015-07-19T14:18:58+08:00

Please refer to the attachment for the illustration.

------------------------------------

Using tangent you'll have:

tan59^0 =  \frac{h}{x-31} \\ (x-31)tan59^0 = h ~~----equation1 \\ tan33^0 =  \frac{h}{x} \\ xtan33^0 = h~~----equation2 \\ equate~1&2 \\ (x-31)tan59^0 = xtan33^0 \\ xtan59^0-31tan59^0 = xtan33^0 \\ xtan59^0 - xtan33^0 = 31tan59^0 \\ 1.01487x = 51.59266 \\ x = 50.8367 \\ ------------- \\ to~find~h~substitute~x~to~equation2 \\ xtan33^0 = h \\ (50.8367)tan33^0 = h \\ h = 33.01375ft.

0